Bacterial Autophagy: Offense and Defense at the HostâPathogen InterfaceSummary - James E. Casanova (Cellular and Molecular Gastroenterology and Hepatology, 2017)
Autophagy is a fundamental cellular process used for the turnover and recycling of cytosolic components and damaged organelles. Originally characterized as a response to cellular stress, it now is well established that autophagy also is used as a defensive mechanism to combat the infection of host cells by intracellular pathogens. However, although this defensive strategy does limit the proliferation of most pathogens within their host cells, successful pathogens have evolved countermeasures that subvert or circumvent the autophagic response. In this review, we discuss the mechanisms used by a number of these pathogens to escape autophagy, with a particular focus on Salmonella enterica serovar Typhimurium, which has been the most extensively studied example. We also discuss the consequences of bacterial autophagy for the broader innate immune response. Keywords: Autophagy, Xenophagy, Salmonella, FAK, Akt, Interferon